2019
DOI: 10.1186/s13068-019-1487-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles carry cellulases in the industrial fungus Trichoderma reesei

Abstract: Background Trichoderma reesei is the most important industrial producer of lignocellulolytic enzymes. These enzymes play an important role in biomass degradation leading to novel applications of this fungus in the biotechnology industry, specifically biofuel production. The secretory pathway of fungi is responsible for transporting proteins addressed to different cellular locations involving some cellular endomembrane systems. Although protein secretion is an extremely efficient pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 97 publications
0
45
1
1
Order By: Relevance
“…Compared to yeasts, little is known about EVs in filamentous fungi. However, their presence has been described in different species, including Trichoderma reesei , a fungus involved in lignocellulosic degradation (de Paula et al, 2019 ), in the phytopathogens Alternaria infectoria (Silva et al, 2014 ) and Fusarium oxysporum f. sp. vasinfectum (Bleackley et al, 2019b ), and in the dermatophyte Trichophyton interdigitale (Bitencourt et al, 2018 ).…”
Section: Extracellular Vesicles In Fungi: Historical Aspects and Overmentioning
confidence: 99%
“…Compared to yeasts, little is known about EVs in filamentous fungi. However, their presence has been described in different species, including Trichoderma reesei , a fungus involved in lignocellulosic degradation (de Paula et al, 2019 ), in the phytopathogens Alternaria infectoria (Silva et al, 2014 ) and Fusarium oxysporum f. sp. vasinfectum (Bleackley et al, 2019b ), and in the dermatophyte Trichophyton interdigitale (Bitencourt et al, 2018 ).…”
Section: Extracellular Vesicles In Fungi: Historical Aspects and Overmentioning
confidence: 99%
“…In 2007, Rodrigues et al, studying Cryptococcus neoformans, initially reported production of EVs by fungi (15). Since then, fungal EV production has been described in several fungal species, such as Cryptococcus gattii (16), Saccharomyces cerevisiae (17), Alternaria infectoria (18), Paracoccidioides brasiliensis (19), Histoplasma capsulatum (20), Candida albicans (20), Candida parapsilosis (20), Sporothrix schenckii (20), Sporothrix brasiliensis (21), Malassezia sympodialis (22), Pichia fermentans (23), Trichophyton interdigitale (24), Trichoderma reesei (25), Aspergillus fumigatus (26), and others.…”
mentioning
confidence: 99%
“…However, Winandy et al 42 showed a similar stability of layers formed on glass by HFBs from both classes, and Hähl et al 61 demonstrated the stability of HFB vesicles formed by HFB1 (class II). Therefore, we speculate that HFBs, as universal and specific fungal proteins, contribute to the formation of extracellular vesicles that attract attention in cell biology as intracellular delivery and communication vehicles 62, as demonstrated in fungi 63 , including Trichoderma 64 .…”
Section: Discussionmentioning
confidence: 95%